Carbon Reduction Program Implementation Strategy on Product Tanker Fleet Against the Carbon Intensity Indicator (CII) Decreasing Target - Wahju Prasetyo, Dwi; Herawati, Susi; Hananto, Tri (International Journal of Advanced Multidisciplinary, 2023)
Emissions of gases released into the atmosphere by various human activities on earth cause a greenhouse effect in the atmosphere. Greenhouse gases include carbon dioxide (CO2), sulfur dioxide (SO2), nitrogen monoxide (NO), nitrogen dioxide (NO2), methane (CH4) and chlorofluorocarbons (CFCs). One activity that increases greenhouse gases is shipping. Shipping is a cost-effective and energy-efficient form of bulk transportation, but currently international shipping operations account for approximately 2.5% of man-made greenhouse gas emissions globally [1]. Therefore, in 2018, IMO's initial strategy was adopted to reduce greenhouse gas emissions from ships by reducing carbon dioxide emissions by at least 40% by 2030 and targeting a reduction of carbon dioxide emissions by 70% by 2050. And reduce annual greenhouse gas emissions from ships by at least 50 percent by 2050 compared to 2008 [2]. To reduce the impact of these activities, IMO issued regulation 28 MARPOL Annex VI if ships with a capacity of 400 Gross Tonnage (GT) or more receive a D rating for three consecutive years or an E rating, corrective action is required to achieve an annual operational CII. er to achieve the desired rating in 2025.